Role Conflict, Role Ambiguity, and Turnover Intention: The Mediating Effect of Work Stress on Female Employees - Rizal Mohamad; Amin Muhammad Sirojuddin; Basalamah Muhammad Ridwan; Wahono Budi (SHS Web of Conferences, 2025)
This research explores the determinants of turnover intention among female employees within the Indonesian cigarette industry, with a specific focus on PT Karya Timur Prima. The industry, a significant contributor to Indonesia’s GDP, employs around 5.98 million workers. Female employees in this industry face unique challenges, such as high production target pressure, frequent role conflicts, and role ambiguity, making it an ideal context to study turnover intention. Drawing on the Theory of Reasoned Action, this study examines the impact of role conflict, role ambiguity, and work stress on turnover intention. A conceptual framework is developed, and hypotheses are proposed based on existing literature. The study employs a quantitative approach with a sample of 232 female employees in PT Karya Timur Prima’s production department. Data is analyzed using PLS-SEM. Results indicate that role conflict and role ambiguity significantly influence turnover intention, both directly and indirectly, through the mediating effect of work stress. The study highlights the vulnerability of female employees to work stress and its impact on turnover intention. Organizational commitment is identified as a potential mitigating factor. The findings emphasize the need for organizations to address role clarity, manage work stress, and foster organizational commitment to reduce turnover intentions among female employees in high-pressure industries like cigarette manufacturing.